Long‐term monitoring of relative displacements at the keystone of a masonry arch bridge. Issue 4 (19th January 2018) - Ataei, Shervan; Nouri, Mehrdad; Kazemiashtiani, Vahid
Summary: Nonstop development of the railway transportation and some demands such as axle load increasing caused many researchers work thoroughly about the sustainable development. It consists of the maintenance of historic structures instead of replacing them. Following the same track, the current research is illustrating the structural health monitoring of a masonry arch railway bridge with the main span of 66 m. The leading concern through this research is the changes in relative displacements of the adjacent blocks. Eccentricity tracing, assessment of the maximum service load, and comparing the changes with the code loading are presented in this paper. Estimation of the dynamic impact factor are among the objectives satisfied by taking advantage of the monitoring data, as well. It is also to rate the efficiency of the applied method in tracing the structural performance of the complex structures like masonry arch bridges.